Quality of life in heart failure. The heart of the matter. A scientific statement of the Heart Failure Association and the European Association of Preventive Cardiology of the European Society of Cardiology - Volterrani, Maurizio; Halasz, Geza; Adamopoulos, Stamatis; Agostoni, Pier Giuseppe; Butler, Javed; Coats, Andrew J.S.; Cohen-Solal, Alan; Doehner, Wolfram; Filippatos, Gerasimos; Jankowska, Ewa A.; Lam, Carolyn S.P.; Lambrinou, Ekaterini; et al. (My University, 2025)
For most patients with chronic, progressive illnesses, maintaining good quality of life (QoL), with preserved functional capacity, is just as crucial as prolonging survival. Patients with heart failure (HF) experience much worse QoL and effort intolerance than both the general population and people with other chronic conditions, since they present a range of physical and psychological symptoms, including shortness of breath, chest discomfort, fatigue, fluid congestion, trouble with sleeping, and depression. These symptoms reduce patients' capacity for daily social and physical activity. Usual endpoints of large-scale trials in chronic HF have mostly been defined to evaluate treatments regarding hospitalizations and mortality, but more recently, patients' priorities and needs expressed with QoL are gaining more awareness and are being more extensively evaluated. This scientific statement aims at discussing the importance of QoL in HF, summarizing the most largely adopted questionnaires in HF care, and providing an overview on their application in trials and the potential for their transition to clinical practice. Finally, by discussing the reasons limiting their application in daily clinical routine and the strategies that may promote their implementation, this statement aims at fostering the systematic integration of the patient's standpoint in HF care.
Keywords: Physical activity; Quality of life; Aging; Chronic disease; Exercise tolerance; Frailty; Functional capacity; Heart failure